2022
DOI: 10.1002/rrq.482
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Dyslexia: How do Different Identification Methods of Parental Difficulties Influence the Conclusions Regarding Children's Risk for Dyslexia?

Abstract: By investigating children whose parents have dyslexia, family risk (FR) studies are expanding our understanding of the intergenerational transmission of dyslexia. These studies, however, vary in their identification of FR, and how the use of different identification methods influences research findings and conclusions is yet to be systematically investigated. This study aims to evaluate the association between two FR identification methods—parental self‐reports and direct skill assessments—and their unique con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For example, Khanolainen et al (2022) showed that parental self-reported difficulties and parental reading skills predict a child's literacy skills at age 23 among the Finnish sample with potential family risk for dyslexia. Using the same sample, Torppa et al (2022) found that shared reading assessed at age 2 predicts vocabulary at ages 3-5 and reading comprehension among children at age 15 indirectly through enhanced motivation. Our results confirmed similar findings for a variety of outcomes on a larger sample under a simpler model with a Bayesian approach.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Khanolainen et al (2022) showed that parental self-reported difficulties and parental reading skills predict a child's literacy skills at age 23 among the Finnish sample with potential family risk for dyslexia. Using the same sample, Torppa et al (2022) found that shared reading assessed at age 2 predicts vocabulary at ages 3-5 and reading comprehension among children at age 15 indirectly through enhanced motivation. Our results confirmed similar findings for a variety of outcomes on a larger sample under a simpler model with a Bayesian approach.…”
Section: Discussionmentioning
confidence: 99%
“…This is a feasible measure that more closely resembles reality compared to a categorical approach by approximating parents’ current and previous reading experiences. Additionally, studies have shown that the use of self‐report questionnaires in parents can be a valid reflection of their actual reading abilities (Bjornsdottir et al., 2014; Khanolainen et al., 2022; Lefly & Pennington, 2000; Vandermosten et al., 2017). Nevertheless, there are also some limitations related to the measure that deserve attention.…”
Section: Discussionmentioning
confidence: 99%
“…The latter task took 3 min and included 60 items, in each of which the participant was instructed to verify the truthfulness of a simple sentence. The total score of children skills was the average of the two fluency tasks' z ‐scores (Cronbach's alpha for the composite = .87) (for more details about the task, see Khanolainen et al, 2022).…”
Section: Methodsmentioning
confidence: 99%